Altered transcriptome and disease-related phenotype emerge only after fibroblasts harvested from patients with age-related macular degeneration are differentiated into retinal pigment epithelium. (June 2021) - Cai, Hui; Gong, Jie; Noggle, Scott; Paull, Daniel; Rizzolo, Lawrence J.; Del Priore, Lucian V.; Fields, Mark A.; ,
Abstract: We have reported previously that retinal pigment epithelium (RPE) differentiated from induced pluripotent stem cells (iPSC) generated from fibroblasts of patients with age-related macular degeneration (AMD) exhibit a retinal degenerative disease phenotype and a distinct transcriptome compared to age-matched controls. Since the genetic composition of the iPSC and RPE are inherited from fibroblasts, we investigated whether differential behavior was present in the parental fibroblasts and iPSC prior to differentiation of the cell lines into RPE. Principal component analyses revealed significant overlap (essentially no differences) in the transcriptome of fibroblasts between AMD and controls. After reprogramming, there was no significant difference in the transcriptome of iPSC generated from AMD versus normal donors. In contrast, the transcriptome of RPE derived from iPSC segregated into two distinct clusters of AMD-derived cells versus controls. Interestingly, mitochondrial dysfunction in AMD-derived RPE was evident after approximately two months in culture. Moreover, these differences in mitochondrial dysfunction were not evident in the parental fibroblasts and iPSC. This study demonstrates an altered transcriptome and impaired mitochondrial function in RPE derived from AMD patients versus controls, and demonstrates these differences are not present in the original fibroblasts or iPSC. These results suggest that pathology in AMD is triggered upon differentiation of parent cells into RPE. More study of this phenomenon could advance the current understandings of the etiology of AMD and the development of novel therapeutic targets. Graphical abstract: Image 1 Highlights: iPSC-RPE differentiated from AMD patients express a disease-related transcriptome. Compared to age-matched controls, mitochondria are dysfunctional in AMD-RPE. Disease-related phenotypes are absent in AMD-derived parental fibroblasts and iPSC. Our model displays AMD phenotypes without extended culture or environmental insults. These data are novel and have not been reported elsewhere in the literature.